2010
DOI: 10.4103/0019-5413.58612
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Gartland type II and type III supracondylar fractures treated by Blount’s technique

Abstract: Background:According to some orthopedic surgeons, almost all supracondylar humerus fractures should be treated operatively by reduction and pinning. While according to others, closed reduction and immobolization should be used for Gartland type II and some type III fractures. However, the limit of this technique remains unclear. We present 74 patients with displaced extension-type supracondylar fractures treated by closed reduction and immobilization with a collar sling fixed to a cast around the wrist. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
(48 reference statements)
0
24
0
3
Order By: Relevance
“…They include immobilisation in an above-elbow backslab or even collar and cuff for undisplaced fractures (Gartland I). In displaced fractures (Gartland II and III) cast immobilisation in either flexion or extension, [3][4][5][6][7][8][9] various forms of traction, including horizontal traction, vertical traction, Dunlop traction, 3,6,[10][11][12][13] skeletal traction through an olecranon pin and traction in pre-fabricated braces have been used. 3,6,14,15 The commonly accepted method involves closed reduction and Kirschnerwire (K-wire) fixation, with variation in number of pins and configuration, either medial and lateral wires or only lateral wires, which can be either parallel or crossed.…”
Section: Outcome Of Displaced Supracondylar Fractures In Children Aftmentioning
confidence: 99%
“…They include immobilisation in an above-elbow backslab or even collar and cuff for undisplaced fractures (Gartland I). In displaced fractures (Gartland II and III) cast immobilisation in either flexion or extension, [3][4][5][6][7][8][9] various forms of traction, including horizontal traction, vertical traction, Dunlop traction, 3,6,[10][11][12][13] skeletal traction through an olecranon pin and traction in pre-fabricated braces have been used. 3,6,14,15 The commonly accepted method involves closed reduction and Kirschnerwire (K-wire) fixation, with variation in number of pins and configuration, either medial and lateral wires or only lateral wires, which can be either parallel or crossed.…”
Section: Outcome Of Displaced Supracondylar Fractures In Children Aftmentioning
confidence: 99%
“…Results of type III were influenced by the direction of displacement: fractures remained stable in 88% of posterior displacements, 58% of posteromedial displacements, and only 36% of posterolateral displacements. 9 Kinkpé et al observed 100% stable fractures and 100% good results in 67 type III fractures. Time to treatment (mean time to referral, 30 hours; mean time to treatment, 46 hours) did not influence anatomic and clinical results.…”
Section: Discussionmentioning
confidence: 97%
“…Some prefer closed reduction and pinning for all displaced supracondylar fractures, including Gartland type II and type III. [4,7] while many agree with open reduction techniques and that type III fractures with a posterolateral displacement are less stable and should be treated by internal fixation 8 .Surgical indications are unsuccessful closed methods, severe displacement, severe ecchymosis in anterior part of elbow, vascular insufficiency and open fractures 6 . Complications are common.…”
Section: Discussionmentioning
confidence: 99%